2021
DOI: 10.1094/pdis-10-20-2182-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fusarium miscanthi Causing Ear Rot on Maize in China

Abstract: Maize (Zea mays L.), an important food and feed crop worldwide, can be infected by Fusarium pathogens that can contaminate grain with mycotoxins. From August to October in 2018 and 2019, a field survey for maize ear rot was conducted in 76 counties of Guizhou province. The incidence ranged from 3% to 15% at individual fields in different areas. A total of 175 diseased maize ears with similar symptoms, including kernels covered with white, pink or salmon-colored mold or exhibiting a white streaking (“starburst”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The most common maize ear rot is caused by fungi in the genus Fusarium, such as Fusarium miscanthi (Tuberculariales: Tuberculariaceae), Fusarium proliferatum (Tuberculariales: Tuberculariaceae), and Fusarium verticillioides (Tuberculariales: Tuberculariaceae) [28][29][30]. Except for Fusarium spp., more than 40 fungal species, such as Aspergillus spp., Trichoderma spp., and so on, have also caused maize ear rot alone or together [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common maize ear rot is caused by fungi in the genus Fusarium, such as Fusarium miscanthi (Tuberculariales: Tuberculariaceae), Fusarium proliferatum (Tuberculariales: Tuberculariaceae), and Fusarium verticillioides (Tuberculariales: Tuberculariaceae) [28][29][30]. Except for Fusarium spp., more than 40 fungal species, such as Aspergillus spp., Trichoderma spp., and so on, have also caused maize ear rot alone or together [37].…”
Section: Discussionmentioning
confidence: 99%
“…Except for YPM, maize is also affected by maize ear rot, which is one of the most prevalent and destructive diseases of maize. The maize ear rot is caused by more than 40 fungal species alone or together, such as Fusarium spp., Aspergillus spp., Trichoderma spp., and so on [28][29][30]. The incidence of maize ear rot is commonly ranged from 5% to 20% in 22 provinces in China's fields [31].…”
Section: Introductionmentioning
confidence: 99%
“…F. concentricum was first reported to cause pepper fruit rot in China ( Wang J. H. et al, 2013 ) and cause maize ear rot in the Guangxi Zhuang Autonomous Region of China ( Du et al, 2020 ). F. miscanthi was first isolated from the straw of Japanese silver grass, Miscanthus sinensis, in Denmark ( Gams et al, 1999 ) and identified to be infectious agent of maize ear rot ( Shang et al, 2021 ). F. cortaderiae was first isolated from pampas grass ( Cortaderia jubata ) ( O’Donnell et al, 2004 ) and subsequently separated from maize grain in New Zealand ( Monds et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%